Human Resource Development at BMT Binamas Purworejo - Setiyono, Ahmad; Nuraini, Rafa Farida (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study aims to describe the process of human resource development (HRD) at BMT Binamas Purworejo, the challenges faced, and the impact of HRD on employee performance. This research used a qualitative descriptive method through field study, involving direct observation, interviews with management and staff, as well as documentation review. The findings show that HRD at BMT Binamas is implemented through routine coaching activities such as SABIT (Sabtu Bina Iman dan Taqwa), MABIT (Malam Bina Iman dan Taqwa), weekly Islamic studies, and joint sports, which focus on strengthening employee capacity in technical, moral, and spiritual aspects. However, HRD programs are still informal and have not been systematically structured into certified training or formal workshops. The main challenges include limited training budgets, lack of specialized trainers, and suboptimal use of digital learning systems. Despite these constraints, HRD has a positive impact on employee loyalty, work ethic, and overall performance. This study highlights the importance of structured, competency-based HRD programs supported by adequate resources and digitalization.